Optimality conditions in problems of control over systems of impulsive differential equations with nonlocal boundary conditions - Sharifov, Ya. A. (Ukrains’kyi Matematychnyi Zhurnal, 2012)
We consider the problem of optimal control in which the state of the controlled system is described by impulsive differential equations under nonlocal boundary conditions, which is a natural generalization of the Cauchy problem. Using the principle of contracting mappings, we prove the existence and uniqueness of a solution of a nonlocal boundary-value problem with pulse action with fixed admissible controls. Under certain conditions for the initial data of the problem, we calculate the gradient of a functional and obtain necessary optimality conditions.